2022
DOI: 10.1177/17407745211069153
|View full text |Cite
|
Sign up to set email alerts
|

The representation of Indigenous peoples in chronic disease clinical trials in Australia, Canada, New Zealand, and the United States

Abstract: Background Indigenous peoples are overrepresented with chronic health conditions and experience suboptimal outcomes compared with non-Indigenous peoples. Genetic variations influence therapeutic responses, thus there are potential risks and harm when extrapolating evidence from the general population to Indigenous peoples. Indigenous population–specific clinical studies, and inclusion of Indigenous peoples in general population clinical trials, are perceived to be rare. Our study (1) identified and characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…People from rural settings (n=28, 14%) 68 70 and people with Pacific Islander; Indigenous and Hispanic heritage were under-represented ( online supplemental table S6 ). Under-representation of these groups is common in clinical research 154–156 despite the disproportionate prevalence of CKD 157–160 and numerous sociogeographical barriers to care such as shortage of health providers and distance from health facilities. 161–163 These factors reflect an urgent need to generate community-specific knowledge and develop accessible healthcare platforms to serve the needs of these disadvantaged groups.…”
Section: Discussionmentioning
confidence: 99%
“…People from rural settings (n=28, 14%) 68 70 and people with Pacific Islander; Indigenous and Hispanic heritage were under-represented ( online supplemental table S6 ). Under-representation of these groups is common in clinical research 154–156 despite the disproportionate prevalence of CKD 157–160 and numerous sociogeographical barriers to care such as shortage of health providers and distance from health facilities. 161–163 These factors reflect an urgent need to generate community-specific knowledge and develop accessible healthcare platforms to serve the needs of these disadvantaged groups.…”
Section: Discussionmentioning
confidence: 99%
“…Differing Indigenous cultures are under‐served across global trials research including those in Australia, Canada, New Zealand, and the United States 26–28 . A 2021 review focused on Indigenous Australians from 2008 to 2018 found that ‘relative to population size and burden of disease, the number of trials focusing on indigenous health is low’ 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Differing Indigenous cultures are underserved across global trials research including those in Australia, Canada, New Zealand, and the United States [26][27][28] . A 2021 review focused on Indigenous Australians from 2008-2018 found that "relative to population size and burden of disease, the number of trials focusing on indigenous health is low" 29 .…”
Section: Discussionmentioning
confidence: 99%